2013
DOI: 10.1007/s00404-013-3092-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of bladder wall thickness as a screening test for detrusor instability

Abstract: In women with lower urinary tract symptom, transvaginal ultrasounds measured mean BWT seems to be an effective non invasive diagnostic tool for prediction of OAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
1
9
1
Order By: Relevance
“…These findings agree with those of Abou-Gamrah et al [10] who reported a 90% sensitivity and a 78% specificity. Tangal et al [11] who performed their study on children reported lower values (67% sensitivity and 80% specificity).…”
Section: Discussionsupporting
confidence: 95%
“…These findings agree with those of Abou-Gamrah et al [10] who reported a 90% sensitivity and a 78% specificity. Tangal et al [11] who performed their study on children reported lower values (67% sensitivity and 80% specificity).…”
Section: Discussionsupporting
confidence: 95%
“…In an update of the systematic review on the diagnostic accuracy of BWT in diagnosing DO (unpublished data: Suneetha Rachaneni, University of Birmingham, 2015) 21 studies 28,[49][50][51][52][53][54][55][56][57][58][59]72,97,[113][114][115][116][117][118][119] have been identified that have investigated the relationship between BWT measured by ultrasonography and DO, results from which for the sensitivity, specificity and AUC for bladder ultrasonography vary from 37% to 91%, 61% to 97% and 0.61-0.91, respectively (see Appendix 7). The studies draw mixed conclusions, ranging from…”
Section: Placing the Results In The Context Of Other Researchmentioning
confidence: 99%
“…49,51,54,57,72,117 Our study is the most conclusively negative study of the diagnostic value of bladder ultrasonography to date.…”
Section: Diagnostic Accuracy Of Bwt Via Bladder Ultrasonography In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…For a mean BWT cut-off of 5 mm, the specificity was reported to be 89% (95% CI 79-96) with a sensitivity of 84% (95% CI 76-90). 16 We identified further studies [19][20][21][22][23][24][25][26][27][28][29][30] which had investigated the relation between BWT measured by ultrasonography and DO, with estimates of sensitivity, specificity and AUC for bladder ultrasound varying from 37-91%, 61-97% and 0.61-0.91, respectively. 8 The published studies are mostly from a single centre (often tertiary) and there are multiple reasons to have concerns about the validity and applicability of findings.…”
Section: Interpretation In Light Of Other Evidencementioning
confidence: 99%